Resolving some nomenclatural issues on 'Isoeto-Nanojuncetea' and four new communities of the Iberian Peninsula - Silva, Vasco; Ribeiro, Sílvia; Molina, Jose Antonio; Pinto-Cruz, Carla; Costa, José Carlos; Espírito-Santo, Dalila (Mediterranean Botany, 2021)
We describe four new vegetation units and propose 17 new typifications and 24 altered names of syntaxa belonging to Isoeto-Nanojuncetea. Information is also provided on the publication dates of the alliances Isoetion and Preslion.